IDEAS AND REALIZATION OF ISLAMIC UNIVERSITY BY AL-ATTAS (CASE STUDY: ISTAC-IIU MALAYSIA) - Huringiin, Nabila (State Institute of Islamic Studies (IAIN) Palu, 2021)
ABSTRACT This article aims to elaborate on the Islamic university idea of Syed M Naquib al Attas (l.1931). To clarify the concept of university, a discussion will also regarding the Institute For the Study of Islamic Thought and Civilization - International Islamic University Malaysia (ISTAC-IIUM) as a realization of his idea of an Islamic university. The writer uses descriptive analysis in understanding al-Attas' ideas; as used comparative analysis with other figures. The result of the research is that the Islamic university is based on concept of perfect man or universal man (insan kamil). This is what applies well in his institution i.e ISTAC-IIUM. When the Islamic university is based on the insan kamil concept, than the aim of the university is to product a perfect man or universal man (insan kamil). Key World: Islamic University, Al-Attas, Insan Kamil, ISTAC-IIUM